Wybory do sejmiku województwa śląskiego w 1998 i 2002. Niespójne województwo - Marmola, Maciej (Instytut Politologii Uniwersytetu Wrocławskiego, 2024)
The first part of the article is a brief introduction, presenting the specifics of the regional political scene in the Silesian Voivodeship. The next section is dedicated to characterizing the main participants in the competition in the regional assembly elections of 1998 and 2002. The article concludes with an analysis of the results of these two elections. Several indices describing the electoral process and its consequences for the regional political scene are used in the article. These include the proportionality index with the determination of the size of the electoral system’s overrepresentation, the competitiveness index, the aggregation index, and the effective number of parties’ index.
Keywords: regional political scenes; Silesian Voivodeship; 1998 and 2002 regional assembly elections; electoral indices; results analysis